CHARACTERISTICS OF SOMATIC AND REPRODUCTIVE HEALTH IN GIRLS WITH DELAYED PUBERTY - Bekbauliyeva, G.N.; Kadirova , B.M.; Ibrakhimova , N.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. Delayed puberty (DP) in adolescent girls represents a significant medical and social problem affecting reproductive potential at the population level. Investigation of somatic status in this patient group is particularly important given the high prevalence of extragenital pathology. Materials and methods. A cohort study was conducted involving 625 girls aged 14-18 years with diagnosed DP. The study employed clinical-anamnestic analysis, statistical data processing methods, and evaluation of follow-up observation systems. Results. High frequency of somatic pathology was identified in medical history: chronic diseases present in 86.9% of cases, comorbid conditions in 43.6%, with infectious diseases predominating (43.3 per 100 examined). Specific characteristics of follow-up observation were established: coverage reached only 26.6% of required levels, with hepatobiliary diseases (64.7%) and thyroid disorders (22.4%) being most prevalent.Significant correlations were found between: a) previous tonsillectomy/appendectomy and gynecological pathology, and b) thyroid diseases and menstrual disorders. Conclusions. The study demonstrated an association between somatic status and reproductive development disorders. The findings justify the need for: improving interdisciplinary collaboration systems, optimizing follow-up observation protocols, and developing preventive programs.